The early investment awareness among muamalat students / Nur Ain Nazihah Muhammad Rizal - Muhammad Rizal, Nur Ain Nazihah (2019)
Investment means the production of goods that produce other goods from an economic perspective. Early Investments are about investors among young people who take part in investments. Percentage of investors among young people is only a small percentage. Therefore, the purpose of this study is to examine the level of awareness among students about initial investment 2) to provide alternatives for students to solve financial problems 3) to know the level of student knowledge about initial investment. Methods for collecting data are quantitative through a questionnaire survey. As a result of the survey found that the percentage of students with high awareness was high but they did not have sufficient financial resources and had no fixed income.